Ergonomic risks to which the Nursing team is exposed in their work practices (Research, Society and Development, 2021)
The objective of this study was to analyze the ergonomic risks to which the Nursing team is exposed in their work practices. This is a narrative review of the literature. The sources for searching the references included the database of the Portal de Periódicos da Coordenação de Aperfeiçoamento de Pessoal de Nível Superior (CAPES), the libraries Scientific Electronic Library Online (SciELO) and the Biblioteca Virtual em Saúde (BVS) and the electronic search engine Google Scholar. The Nursing is one of the classes considered most conducive to the occurrence of occupational risks, especially ergonomic ones. The main ergonomic risks observed for professionals in this area are weight lifting, inadequate posture, as well as physical effort at work. The employee who is also exposed to intense working hours suffers from physical exhaustion that, over time, can become a health problem, causing stress, demotivation, drowsiness, drop in work quality and low self-esteem. Preventive measures based on ergonomics and continuing education are necessary to provide better working conditions and quality of life for professionals.